Political prisoners and Conintes prisoners: the investigations in the Chamber of Deputies during Frondizi ´s government (1958-1962) - Castronuovo, Sabrina (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2018)
The aim of this article is to analyse the role of institutions and other places of confinement in the context of political persecution and detention during Frondizi's presidency. Prisons were a central tool to deal with political opposition and to control it. Through the differential use penal institutions according to the type of political prisoner, the different procedures for detention and the circuits of constant transfer of detainees, the use of torture, we infer the fundamental role that penal institutions and other places of confinement occupied.